Antigravity muscle density on computed tomography and health-related independence in normal weight patients with chronic obstructive pulmonary disease - Satoru Terada; Naoya Tanabe; Tomoki Maetani; Yusuke Shiraishi; Kunihiko Terada; Hiroshi Shima; Tsuyoshi Oguma; Ryo Sakamoto; Megumi Kanasaki; Izuru Masuda; Atsuyasu Sato; Susumu Sato; et al. (Respiratory Research)
Abstract Background Low body mass index (BMI) is a prognostic factor, and skeletal muscle adiposity may affect mortality irrespective of BMI in patients with chronic obstructive pulmonary disease (COPD). However, the association between muscle adiposity and healthy life expectancy in normal-weight patients remains unestablished. Objective To examine whether lower chest computed tomography (CT)-assessed erector spinae muscle density (ESMD), which represents antigravity muscle adiposity, is associated with subsequent loss of health-related independence in normal-weight patients with COPD. Methods The ESMD lower limit of normal (LLN) was determined in 194 healthy subjects undergoing lung cancer screening CT. In a prospective cohort of patients with COPD undergoing baseline inspiratory/expiratory CT, the onset of loss of health-related independence, requiring long-term nursing facility or home nursing/medical care, was recorded over 5 years. Results Smokers with COPD (n = 199) were divided into 4 groups on the basis of BMI and the ESMD–LLN: underweight (n = 22), normal-weight with (n = 40) and without (n = 81) low ESMD, and overweight (n = 56). Greater airway wall thickening was associated with BMI-independent low ESMD. A multivariable Cox proportional hazards model including only normal-weight patients with COPD (n = 121) indicated that low ESMD was independently associated with a higher loss-of-independence rate after adjusting for FEV1, COPD assessment test score, and a smaller cross-sectional area of erector spinae muscles (hazard ratio [95% confidence interval] = 3.21 [1.30–7.89]). Conclusion Low antigravity muscle density could reflect airway wall thickening and shorten healthy life expectancy in normal-weight patients with COPD.